Analisis Pelaksanaan Kemitraan Bisnis dengan Pendekatan pada Hubungan Go-Jek dan Pengemudi - Sukmaningrum, Deva (UM Purwokerto Press, 2024)
Current technological developments are closely related to people's lives, and are often linked to globalization which has enabled us to directly obtain information from various corners of the world. Technological advances such as transportation, cellphones and the internet have been widely used not only by people in cities but also by rural residents. An example of a company in the online transportation services sector is “PT. Aplikasi Karya Anak Bangsa is better known as Go-jek. Go-Jek is a company that is leading change in the motorcycle taxi industry by focusing on social aspects. This employment system cannot be separated from what is called an agreement. The form of the PT Gojek partnership agreement includes business relationships and a protection system. For this reason, online motorcycle taxi drivers need legal protection if they have an accident while working. Based on the legal issues above, researchers are interested in conducting research on Analysis of the Implementation of Business Partnerships with an Approach to Go-Jek and Driver Relationships. This research uses a normative juridical method, which looks at legal provisions in legislation. In this research, the Statue Approach is used. The statutory regulations used as primary legal material consist of Law Number 13 of 2003 concerning Employment, as well as Article 1338 relating to Article 1320 in the Civil Code.